Mobility and Identity Construction in Bharati Mukherjee’s Desirable Daughters “The Tree Wife and Her Rootless Namesake” - Miller, Katherine (Studies in Canadian Literature / Études en littérature canadienne, 2004)
Identity politics permeate Bharati Mukherjee's texts, often finding resonance with recent feminist and geographical theory emphasizing the interrelatedness of space, place, subjectivity, and gender. In Desirable Daughters, the ancestral story of a young girl married to a tree and confined for life to her father's compound becomes a touchstone for the present-day characters, raising questions as to whether mobility truly offers these women a way of redefining their identities. The novel ultimately suggests that one's birthplace does form one's identity, and that identity performance remains constrained within the ideological determinants of home and community.